1997
DOI: 10.1038/sj.onc.1200938
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of coding sequences of the entire transforming growth factor beta type II receptor gene in sporadic human colon cancer using genomic DNA and Intron primers

Abstract: Mutations in the transforming growth factor beta type II receptor (TGFb RII) gene have been detected in several human cancers exhibiting microsatellite instability. To extend analyses of this gene, we previously investigated the exon-intron organization of the TGFb RII gene and de®ned seven exons and¯anking intron sequences. In this study, we further determined the nucleotide sequences surrounding these seven exons and designed eight sets of intron-based primers to examine the entire coding region of the TGFb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 6 publications
(7 reference statements)
3
21
0
Order By: Relevance
“…We found poly-adenine tract mutations in three colon cancers with MI; four other colon cancers and all other cell lines had neither RII mutations nor MI (see Table 1). This is consistent with our own series of sporadic tumors of the colon (Takenoshita et al, 1997a), lung (Takenoshita et al, 1997b), pancreas, breast and liver (Vincent et al, 1996), and recent literature reports Wang et al, 1995;Garrigue-Antar et al, 1995;Lu et al, 1995;Parsons et al, 1995;Myero et al, 1995).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…We found poly-adenine tract mutations in three colon cancers with MI; four other colon cancers and all other cell lines had neither RII mutations nor MI (see Table 1). This is consistent with our own series of sporadic tumors of the colon (Takenoshita et al, 1997a), lung (Takenoshita et al, 1997b), pancreas, breast and liver (Vincent et al, 1996), and recent literature reports Wang et al, 1995;Garrigue-Antar et al, 1995;Lu et al, 1995;Parsons et al, 1995;Myero et al, 1995).…”
supporting
confidence: 90%
“…We selected 24 cell lines established from human cancers of the lung, colon, breast, leukemia, head and neck, cervix, pancreas, prostate and retina; all have been shown to be resistant to growth inhibition by TGF-b (Fynan and Reiss, 1993). We tested three mutational hotspots in exons 3, 5 and 7 of the RII gene because four di erent groups analysed complete coding sequences of RII in colon Takenoshita et al, 1997a) and squamous tumors (Garrigue-Antar et al, 1995) and found mostly deletions in the poly-adenine tract (exon 3), occasional missense mutations in exons 5 or 7, and wild type sequences in exons 1, 2, 4 and 6. To analyse genomic DNA samples, we used a novel, rapid sequencing protocol to determine the genomic structure of the RII, designed intron primers for PCR ± SSCP analysis (Takenoshita et al, 1996) and developed a non-isotopic PCR ± SSCP assay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic structure of the TGF-b RII gene and the nucleotide sequences of the¯anking introns for all seven exons were previously determined by PCR-based methods (Takenoshita et al, 1997). The ®rst PCR analysis using speci®c primers for each exon demonstrated that only exons 1 and 2 of TGF-b RII in SNU-5 and exons 1, 2 and 3 in SNU-668 ( Figure 2A) could be ampli®ed.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the 567 amino acid size of normal TGF-b RII which includes 298 amino acid serine/threonine kinase domain encoded by exons 4, 5, 6, and 7, this truncated protein (97 amino acids) would be predicted to be unable to transduce a (Takenoshita et al, 1997) speci®c for each exon of the TGF-b RII gene. In SNU-5, exons 1 and 2 are ampli®ed and in SNU-668, exons 1, 2 and 3 were ampli®ed.…”
Section: Resultsmentioning
confidence: 99%